UJI PERFORMANCE BIOFILTER ANAEROBIK UNGGUN TETAP MENGGUNAKAN MEDIA BIOFILTER SARANG TAWON UNTUK PENGOLAHAN AIR LIMBAH RUMAH POTONG AYAM - Said, Nusa Idaman; Firly, Firly (Center for Environmental Technology, 2005)
An experiment of anaerobic biofilter using honeycomb plastic media was conducted in semi-pilot scale. This paper describes the pilot plan study of chickenÃ¢â‚¬â„¢s slaughterhouse wastewater treatment using anaerobic and aerobic submerged biofilter using honeycomb plastic media. The main research was conducting by continuous operation under condition 4 days, 2 days and 1 day retention time. The result of experiment shows that within the anaerobic process under conditions 1- 4 days retention time, the removal efficiency of COD were 78 Ã¢â‚¬â€œ 87 %, BODÃ‚Â were 78 Ã¢â‚¬â€œ 89Ã‚Â Ã‚Â %, 73 Ã¢â‚¬â€œ 83 % , and Total Suspended Solids (TSS) were 83 Ã¢â‚¬â€œ 96 %Ã‚Â respectively.Ã‚Â Using combined anaerobic and aerobic process under same conditions 1 - 4 days retention time shows increasing of removal efficiency.Ã‚Â The removal efficiency of COD were 86 Ã¢â‚¬â€œ 90 %, BOD were 85 Ã¢â‚¬â€œ 90 %, Organics (KMnO4) were 81 Ã¢â‚¬â€œ 88 % and Total Suspended Solids (TSS) were 94 Ã¢â‚¬â€œ 96 % respectively.Ã‚Â The longer retention time has resulted in higher removal efficiency.Ã‚Â Kata Kunci : Biofilter anaerobik, media sarang tawon, air limbah, rumah potong ayam.